Model kinerja perawat pelaksana terhadap peningkatan mutu pelayanan keperawatan - Nita Puspita; Erlena Erlena (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: The quality of a hospital as an institution that produces healthcare technology products depends on the quality of medical services and nursing services provided to patients.Purpose: To find out the nurse's performance model for improving the quality of nursing services for health insurance (BPJS participants) Method: The study is a descriptive-analytic study that used a cross-sectional design. The sampling technique of the study was consecutive sampling and the sample of the study is inpatients in Karawang Regional General Hospital that used health insurance (BPJS participants) a total of 335 respondents. Data were analyzed using Partial Least Square (PLS).Results: There is a significant effect of nurses’ performance against improving the quality of nursing service with a path coefficient of 0.233 and a T-statistic of 2,342. Psychological factors with indicators of perception, role, personality, motivation, and job satisfaction have a positive effect on performance with a path coefficient of 0,536 and T-statistic is 4,983, and a significant α=5%. The value of the T-Statistic is above the critical value (1,96).Conclusion: The psychological factor of a nurse in providing nursing services significant correlation value of nurses’ performance. Keywords: Performance; Nursing services; Quality; Health insurance (BPJS participants)Pendahuluan: Kualitas suatu rumah sakit sebagai institusi yang menghasilkan produk teknologi jasa kesehatan sudah tentu tergantung pada kualitas pelayanan medis dan pelayanan keperawatan yang diberikan kepada pasien.Tujuan: Mengetahui model kinerja perawat pelaksana terhadap peningkatan mutu pelayanan keperawatan pada pasien BPJS di Ruang Rawat Inap RSUD Karawang.Metode: Deskriptif analitik dengan rancangan cross sectional dan Teknik pengambilan sample dalam penelitian ini adalah consecutive sampling. Sample penelitian ini adalah pasien Rawat Inap di RSUD Karawang dengan jaminan kesehatan BPJS sebanyak 335 responden. Analisa data dilakukan dengan menggunakan PLS.Hasil: Ada pengaruh yang signifikan kinerja perawat terhadap peningkatan mutu pelayanan keperawatan dengan nilai path coefficient 0,233 dan T- statistic 2,342. Faktpr psikologi dengan indicator persepsi,peran,kepribadian,motivasi dan kepuasan kerja berpengaruh positif terhadap kinerja dengan nilai path coefficient 0,536 n nilai T-Statistic sebesar 4,983 dan signifikan pada α=5%. Nilai T-Statistic tersebut berada di atas nilai kritis (1,96).Simpulan: Semakin baik factor psikologi seorang perawat dalam memberikan pelayanan keperawatan maka semakin baik nilai kinerja perawat. Serta semakin baik kinerja perawat maka semakin baik mutu pelayanan di RSUD Karawang.